Irrig‐OH: An Open‐Hardware Device for Soil Water Potential Monitoring and Irrigation Management†. (5th April 2016) - Masseroni, Daniele; Facchi, Arianna; Depoli, Edoardo Vannutelli; Renga, Filippo Maria; Gandolfi, Claudio
Abstract: Sustainability of irrigation practices is an important objective to be pursued in many countries, especially in regions where water scarcity causes strong conflicts among different water uses. The efficient use of irrigation water is a key factor in coping with the food demands of an increasing world population and with the negative effects of climate change on water resource availability in many areas. In this complex context, it is important that farmers can rely on instruments and practices that enable a better management of water at the field scale, whatever the irrigation method they adopt. In this paper, we present an open‐hardware device based on the Arduino technology that was developed to allow the continuous monitoring of soil water potential in the root zone for supporting irrigation scheduling at the field scale. The structure of the device is flexible and can be adapted to host different types of sensors. The results, obtained managing irrigation in a peach orchard, show that adoption of the device, together with a simple irrigation scheduling criterion, allowed a significant increase of water use efficiency without causing a reduction of the quantity and quality of crop production. Copyright © 2016 John Wiley & Sons, Ltd.